Social work practice in nontraditional urban settings - Delgado, Melvin (New York ; Oxford : Oxford University Press, 1999)
The author suggests that many communities can be best served through their own, already-established recreational, social, and cultural centres, and shows how professional social workers can use these non-traditional settings - bars, beauty shops, and bathhouses - to reach out to the communities they are trying to help.
Includes bibliographical references and index.
Description based on print version record.
Keywords: Social case work; Sociology, Urban